Relatedness of Maize streak virus in maize (Zea mays L.) to some grass isolates collected from different regions in Nigeria - Oluwafemi, S.; Alegbejo, D.M.; Onasanya, A.; Olufemi, O (Academic Journals, 2011)
Maize streak virus (MSV; family Geminiviridae, genus Mastrevirus) is the most important virus of maize (Zea mays L.) in sub-Saharan Africa. The relatedness of this virus to others showing streak symptoms from grasses on or near maize fields from five ecological areas of Nigeria was studied using genetic scanning analyzer. The relationship dendogram showed 50-95% variations as the 30 isolates were grouped into two main clusters at 0.50 coefficient of variation, five subgroups at 0.06 and 25 at 0.95 coefficient of variation, respectively. The dendogram suggests five family trees at 60% similarity. Split decomposition data showed three clusters implying three evolutionary trees among the streak isolates in Nigeria, as indicated by the three major groupings. The first cluster had four subgroups. MSV (IITA) is within the first tree, which also had 14 other grass isolates. The second tree comprised only three isolates, which were all transmissible to maize and produced typical or severe symptoms in their grass hosts. The third tree had 12 isolates, which were diverse from each other. Despite basic differences in the theoretical background of UPGMA cluster analysis and Split Decomposition, these two approaches of phylogeny reconstruction yielded similar result